Social Capital in Maintaining Harmony in Multicultural Communities in Wanasari Hamlet, Denpasar, Bali - Azharghany, Rojabi; Cantika Yulia Rachmawati; Dodik Harnadi (Program Studi Pendidikan IPS Unesa, 2025)
Indonesia is a country that has a diversity of ethnic races, religions, cultures and languages. Differences in entities allow social disintegration between individuals and groups. This can be prevented through social capital owned by multicultural communities in Kampung Jawa. This study aims to understand the role of social capital in shaping inter-ethnic harmony and integration in preventing conflict in the Javanese village in Wanasari Hamlet. The theory used in this research is social capital proposed by Fukuyama and reinforced by Pierre Bordieu. The method used is a qualitative method with a descriptive approach. Data collection was carried out through the observation stage of interviews and documentation with research subjects selected using purposive sampling. The results of this study explain that the Javanese Village Community with different ethnic backgrounds can live side by side and the social capital that is present to control conflicts include trust through a cultural approach, prevailing community norms, social networks that strengthen solidarity and community participation in various activities. These three components foster positive values in the Kampung Jawa community such as the value of togetherness, cooperation and reciprocal relationships in terms of goodness among the community. Thus, social capital plays an important role in fostering harmony, maintaining positive relationships and minimizing conflict.